Forensic Monitoring Project Report: Bradina Exhumations Republika Srpska Commission on Missing and Tracing - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Harrington, Richard From April 25-27 the Republika Srpska Commission on Missing and Tracing conducted exhumations in and near the town of Bradina. The purpose of the exhumations was to recover approximately 30 of more than 50 Bosnian Serbs reported to have been killed in the area by Bosnian Muslim military personnel in May of 1992. 22 bodies were recovered from a mass grave south of a church and eight bodies from individual graves north of the same church. The recovered remains are believed to be Bosian Serbs killed by Bosnian Muslim military personnel in May of 1992. Place of Exhumation: Bradina Date of Exhumation: 25-27 April 1998 Minimum Number of Exhumed Individuals: 030